(untitled) (Research, Society and Development, 2022)
This study is an exploratory and descriptive field research, which described the anatomopathological variations found in the lungs of dissected cadaveric specimens. The research was carried out at the Human Anatomy Laboratory of the Faculdades Nova Esperança (FACENE/FAMENE), in the city of João Pessoa, state of Paraíba. The sample consisted of cadaveric parts from the aforementioned laboratory. The analysis was carried out by collecting data, directly from the pieces, and recording through a digital camera, in order to observe the variations and compare with the data consolidated in the theoretical references obtained. Data collection was carried out after the project was approved by the Ethics and Research Committee of FACENE/FAMENE, in December 2021. Subsequently, a verification of the data obtained with the theoretical reference in databases was carried out, determining the impact of variations in cadaveric findings. The present research respected the ethical aspects recommended by CNS Resolution 466/2012, as well as Resolution 1931/2009 CFM, Chapter XII, deals with teaching and medical research.